Implantação e pós-ocupação de obras residenciais em relação à sustentabilidade do ambiente urbano: uma proposta de manual de arquitetura residencial sustentável - Silva, Ana Liria (2019)
Civil construction is one of the human activities that most pollute and degrade the environment. From this premise one perceives the necessity to investigate the factors, causes and consequences pertinent to the action of building that provoke negative environmental impacts. The study aims to focus on the construction of residential single-family buildings in Brazil, which can cause and promote negative impacts from its design that last throughout its life cycle. Thus, starting from the architectural project in its conception, it contemplates its proposal of low plant and implantation as well as its immediate surroundings, important factors for resilience in the urban environment. The next step is to recognize in the residential building, the construction materials used in the execution of the work and the consequent generation of waste. Considering these exposed facts investigated, one begins with the attitudes and concretions that are necessary in all the stages of design and construction of the building so that it can be considered a sustainable construction. In this process the rescue of concepts of Sustainable Architecture, Bioclimatic Architecture and Passive House were investigated and contemplated to highlight the importance of the work appropriating the use of local climate, renewable energy, sustainable materials, natural ventilation and efficient architectural elements that contemplate and promote sustainable development encompassing its three pillars: economic, social and highlighting the environmental. After this research stage the research proposes the "Manual of Sustainable Residential Architecture", which presents principles and paths for all stages of a residential building that respects the environment and contributes positively and meaningfully to the urban environment.